Housing finance and housing needs in Iraq with reference to some Arab experiences - **, د.اكرام عبدالعزيز; الملاحويش, أ.د.لؤي طه محمد رشيد (Journal of Planner and Development, 2008)
the financial resources represent a basic factor of production ;It is obvious that the housing sector needs the resources to finance the building operation to produce all the housing units. Finance is the cornerstone of any housing strategy , as its successes dependent on the success of the financing methods and the creation of charnels and effective methods for the provision of the required finances for both individuals and instantly concerned with the production of housing units. The kinds of financial institutions vary from one country to another according to the nature of the economic and financial system. The lending conditions also vary as well as the capital cost of the housing units needed The housing operations is concerned with many basic factors including that of social and national  concern which affect lending policies